Ultra-dispersed iron powders as catalysts of liquid hydrocarbons synthesis by fischer-tropsch method; Chemical Reactors (CHEMREACTOR-22) - Burlutsky N. P. Nikita Pavlovich; Levashova A. I. Albina Ivanovna; Popok E. V. Evgeniy Vladimirovich; Zhuravkov S. P. Sergey Petrovich; Polonskaya M. S. Marina Sergeevna (2016, 2016)
Title screen